Sentimental analysis on social media data using R programming - Geetha Bhargava, Mandava; Rajeswara Rao, Duvvada (International Journal of Engineering and Technology, 2018)
Sentimental Analysis is an ongoing research field in Text Mining Arena to determine the situation of market on particular entity such as Product, Services...Etc. and it can be called as computational treatment of reviews, subjectivity and sentiment of text. Cryptocurrency can be explained as a type of digital estate and devised to mechanize as a form of trade and exchanges that uses cryptography as an encryption technique to secure the transactions and acts as decentralized controlled transaction which is opposed to centralized transactions. Cryptocurrency are a type of virtual currency, digital currency and alternative currency, On basis of categorical, there are different architecture and security protocols which are used in the cryptocurrencies to secure transactions, the different types of cryptocurrency are available in the market such as Bitcoin, Litecoin, and Namecoin…etc. This paper focuses on survey on different types of sentimental analysis methods and main contribution of this paper include sentimental analysis of  social media data on different types of cryptocurrencies on basis of categorical and different terms of cryptocurrency such as Cryptocurrency, virtual currency, digital currency and discussed on trends of crypto currency in present market.